Ijtihad by Ra’y: the main source of inspiration behind Istihsan - Kayadibi, Saim (Association of Muslim Social Scientists, 2007)
This essay investigates the implementation of istihsan (juristic preference) in the early history of Islam by identifying the concept of ijtihad (independent effort) and ra’y (juristic opinion),both of which played an enormous role in the development of Islamic law. Ijtihad by ra’y (personal judgment in juridical judgment)has been practiced from the time of the Prophet, as reflected in several hadiths narrated by Mu`adh ibn Jabal (d.18/640). The Prophet taught him how to use personal discretion and encouraged the Companions to undertake ijtihad by ra’y with regard to various issues. The criteria of personal judgment in istihsan indicate a direct relationship between istihsan and ijtihad by ra’y. The nature of istihsan, the wisdom behind it, and the wisdom of its use is quite considerable. As istihsan is considered a product of ijtihad, it represents simplicity, ease, and the lifting of difficulties. If the resulting qiyas (analogy) is not in keeping with the Shari`ah’s spirit, then the ruling of similarities should be abandoned in order to give a ruling according to the special evidence that justifies its spirit. The definitions of istihsan, ijtihad, and ra’y; the historical perspective of ra’y; the validity of ijtihad and its implementation at the time of the Prophet and the Companions; and the practices of ijtihad in terms of istihsan among the Companions are all explored in this paper.